Konstruksi Literasi Keagamaan dalam Tafsir The Study Qur’an - Al-Ayyuubi, Mohammad Salahuddin; Haris, Abdul (Sunan Kalijaga Islamic State University, 2024)
This study investigates how The Study Quran, a commentary led by Seyyed Hossein Nasr, represents religious literacy within the framework of religious and cultural diversity. Employing a qualitative methodology, the research examines this commentary to delineate the concept of religious literacy and illustrates how this concept is manifested in the commentary's interpretation. The findings reveal that